Helicobacter pylori isolated from patients with tonsillar cancer or tonsillitis chronica could be of different genotype compared to isolates from gastrointestinal tract - Pavlík, E; Lukes, P; Potuzníková, B; Astl, J; Hrdá, P; Soucek, A; Matucha, P; Dosedĕl, J; Sterzl, I (Folia microbiologica, 2007)
Helicobacter pylori from patients with different diseases, including so-called autoimmune thyroiditis, chronic tonsillitis and tonsillar cancer, was isolated and cultured. It was identified according to the genotype using labeled hybridization probes complementary to six sequences of cagA and vacA genes. Different types of strains were found in isolates from gastrointestinal tract and patients suffering from thyroiditis. Six out of seven genotyped isolates from patients in our Department of Otorhinolaryngology and Head and Neck Surgery exhibited the same genotype, differing from isolates obtained from other patients; the 7th isolate originated from a patient who had undergone surgery for deviatio septi nasi, at the same time suffering from autoimmune thyroiditis, having confirmed gastric infection by H. pylori from biopsy. This data made it possible to formulate the hypothesis on probable association of specific H. pylori genotype with chronic tonsillitis and tonsillar cancer. We assessed commercial transport media and improved nucleic acid isolation techniques and the RT-PCR-based tests, which allowed us to skip a culture step and to test directly the patients' samples; however, for full confirmation of our hypothesis and explanation of possible mechanisms of the contribution of Helicobacter sp. to the pathogenesis of the disease further data are to be collected and evaluated.
Keywords: autoimunitní tyreoiditida; Antigens, Bacterial; Humans; tonzilární nádory; Chronic Disease; Female; polymerázová řetězová reakce s reverzní transkripcí; antigeny bakteriální; Genotype; lidé; Tonsillitis; Reverse Transcriptase Polymerase Chain Reaction; Culture Media; bakteriální proteiny; kultivační média; tonzilitida; Thyroiditis, Autoimmune; ženské pohlaví; Helicobacter Infections; Helicobacter pylori; Male; chronická nemoc; infekce vyvolané Helicobacter pylori; Bacterial Proteins; genotyp; Tonsillar Neoplasms; mužské pohlaví; Gastrointestinal Tract; gastrointestinální trakt